(untitled) (Salam International Academic Journal, 2026)
The migration of academic professionals from Afghanistan’s public universities has escalated following the political transition of August 2021, presenting critical challenges to the country’s higher education system. This qualitative study explores the motivations, lived experiences, and institutional consequences of teacher migration, drawing on semi-structured interviews with 11 university faculty members who relocated abroad. Thematic analysis, guided by Braun and Clarke’s (2006) framework, was employed to categorize findings across personal, organizational, and national dimensions. The analysis revealed that political instability, economic insecurity, limited academic freedom, and concerns for family safety were key factors influencing migration decisions. Participants also cited low salaries and the lack of research opportunities as significant push factors. The departure of experienced faculty has led to a decline in educational quality, loss of institutional knowledge, and weakened research capacity within universities. To mitigate these effects, the study recommends coordinated action by the Afghan government, university leadership, and international stakeholders. Specific measures include fostering institutional security through higher education reforms, enhancing economic incentives, safeguarding academic freedom, and expanding opportunities for professional growth. Moreover, the study underscores the importance of engaging the Afghan academic diaspora through structured knowledge-exchange initiatives, virtual collaborations, and short-term academic projects. While the implementation of these recommendations may face constraints such as limited funding and political uncertainty, their gradual adoption offers a pathway toward stabilizing and revitalizing Afghanistan’s higher education sector.